Efforts to Improve Learning Outcomes Meroda In Floor Exercise Learning Through Teaching Style Command On High School Student Class XI GKPS 1 Simalungun Pematang Raya Academic Year 2015/2016: Efforts to Improve Learning Outcomes Meroda In Floor Exercise Learning Through Teaching Style Command On High School Student Class XI GKPS 1 Simalungun Pematang Raya Academic Year 2015/2016 - Boby Helmi; Juni Ardi Saragih (Journal of Midwifery and Nursing, 2020)
This study aims to determine the improvement of learning outcomes through the implementation of teaching style Meroda command graders XI High School GKPS 1 Simalungun Pematang Raya Academic Year 2015/2016. This study is a class XI student of the sample with the number of students as many as 28 people who will be given the action in the form of learning through the application of the teaching style of command to the learning outcomes meroda gymnastics floor. To obtain the data in this research achievement test at the end of each cycle of the application in the form of learning outcomes assessment tests meroda gymnastics floor. With the implementation of the research achievement test was carried out for two weeks or two meetings. Data analysis was performed with data reduction and exposure data. The study concluded: Of the 28 students there are 8 students (28.57%) who have reached the level of mastery learning with the average value of 55.17% of student learning outcomes. The results of the first cycle are 18siswa (64, 28%) of the 28 students, who have reached the level of mastery learning with the average value of 68.14% of student learning outcomes. In the second cycle 25 students (89.28%) of the 28 students who have reached a level of mastery learning with an average value of 79% can be seen that student learning outcomes from initial tests to do the first cycle and the second cycle there is an increase, it can be said through the application of this teaching style command can improve student learning outcomes.